Progress in Cryptology - INDOCRYPT 2008 9th International Conference on Cryptology in India, Kharagpur, India, December 14-17, 2008. Proceedings - Rijmen, Vincent; Chowdhury, Dipanwita Roy; Das, Abhijit (Security and Cryptology ;, 2008)
This book constitutes the refereed proceedings of the 9th International Conference on Cryptology in India, INDOCRYPT 2008, held in Kharagpur, India, in December 2008. The 33 revised full papers were carefully reviewed and selected from 111 submissions. The papers are organized in topical sections on stream ciphers, cryptographic hash functions, public-key cryptography, security protocols, hardware attacks, block ciphers, cryptographic hardware, elliptic curve cryptography, and threshold cryptography.